Dari Jalan Gelap Menjadi Terang Bagaimana Plang Nama Sederhana Membuat Perbedaan Besar Di Rt 07 Rw 04 Kelurahan Betungan Kuliah Kerja Nyata Tematik (KKNT) Universitas Dehasen Bengkulu Periode Vl - Roki Bimantoro; Kurniawan Kurniawan; Nahdiyah Arenta Cahaya Sakti; Imelia Arista Putri; Edwar Deva Ervansyah; Yanto Effendi; Asnawati Asnawati; Liza Yulianti (Universitas Dehasen Bengkulu, 2026)
Regional identity is an essential element in building a sense of community and facilitating public orientation in daily life. However, not all areas have clear markers, which often creates difficulties for both residents and visitors in identifying territorial boundaries. The installation of RT name signs aims to provide clear identification for the RT 07 RW 04 area in Betungan Sub-district while increasing residents' sense of ownership and pride in their environment. The methods used include location surveys, discussions with community leaders, design and production of name signs, and installation at strategic, easily visible points. The results indicate that the installation of name signs has positive impacts, including easier area identification for residents and guests, improved environmental aesthetics, and strengthened community identity. Additionally, this activity strengthened social interaction through collective work and increased residents' awareness of the importance of territorial administrative order. Thus, installing name signs can be a simple yet meaningful step in building an organized, easily recognizable environment with a strong identity. Betungan Sub- district, specifically RT 07 RW 04, previously had no clear markers on each street and alley, so we from KKN-T took the initiative to participate in making and installing name signs. This activity was accompanied by the Head of RT 07 and local residents. Our hope is that with these name signs, the RT 07 area can be more easily recognized, facilitate access for guests or officers visiting, and most importantly, increase residents' pride in their own environment. We hope these signs will continue to be maintained and become part of a better RT 07 identity going forward.